Exploring the Implementation of Entrepreneurial Values to the Young Farmers in West Java - Kurniawan, Kurniawan; Iskandar, Yusuf; Maulana, Agung (Universitas Mercu Buana, 2024)
Objectives: The objective of this research is to study and explore the implementation of entrepreneurial values among young farmers in West Java and its relationship with empowerment programs, capital structure, self-reliance, and innovation in agriculture. Methodology: A sample of 103 young farmers from various districts in West Java participated in the study. Quantitative analysis, including descriptive statistics, reliability analysis, and path analysis using Smart PLS, was conducted to examine the relationship between entrepreneurial values, self-reliance in agriculture, and innovation in agriculture. Finding: The findings show that young farmers in West Java exhibit moderate levels of entrepreneurial values, with particular emphasis on initiative and creativity. In addition, the analysis shows a positive correlation between entrepreneurial values and empowerment programs, capital structure, self-reliance in agriculture, and innovation in agriculture. The analysis further confirmed that entrepreneurial values are significantly predicted by empowerment programs, capital structure, innovation, and self-reliance in agriculture among young farmers. This study also shows that self-reliance could directly predict entrepreneurial values without capital structure as an intervening variable. These findings highlight the importance of fostering entrepreneurial values among young farmers through empowerment program intervention, providing access to capital structure, promoting agricultural innovation, and encouraging their self-reliance. Policymakers and stakeholders in agriculture should focus on providing training programs and support mechanisms that can foster an entrepreneurial mindset and skills among young farmers in West Java.Conclusion: The need to promote entrepreneurial values among young West Java farmers by boosting empowerment programs, self-reliance, and agricultural innovation with the support of capital structure access. The agricultural sector may become more robust, flexible, and sustainable, boosting regional growth and wealth. Further research should examine how entrepreneurial ideals affect self-reliance and creativity in agriculture and how young farmers might adopt them.